Nephroprotective and Hepatoprotective Effects of Turmeric in Diethylene Glycol Induced Toxicity in Rats - Ekowati, Heny; Devitasari, Arinda; Fitriani, Novita Inawanda; Endriastuti, Nialiana Endah; Wijaya, Triyadi Hendra (Majalah Obat Tradisional, 2025)
In 2022, children in Indonesia experienced acute renal failure due to antipyretic syrup contaminated with diethylene glycol (DEG). DEG is a known contaminant in pharmaceutical solvents that can induce inflammation and act as a free radical, leading to kidney and liver damage. Turmeric (Curcuma Longa) has been reported to have nephroprotective and hepatoprotective effects due to anti-inflammatory and antioxidant properties. This study aims to evaluate the protective effects of turmeric ethanol extract on rat kidneys and liver subjected to DEG toxicity. Rats were divided into five groups (n=5 per group): Group I served as the normal control, while Group II received DEG orally at 3 g/kg BW twice daily for three days. Groups III, IV, and V were treated with DEG (3 g/kg BW) along with turmeric ethanol extract at a doses of 100, 200, and 400 mg/kg BW, respectively, administered orally twice daily for six days. After 14 days, all rats were sacrificed for macroscopic and microscopic evaluation using hematoxylin-eosin (H&E) staining. The results showed that rats treated with turmeric extract exhibited significantly significantly less kidney and liver damage (p<0.05). Kidney protection was evidenced by improvements in endothelial tissue, glomeruli, and tubules, while liver protection was indicated by reduced Kupffer cell activation, sinusoidal dilatation, hepatocyte degeneration, and necrosis. In conclusion, turmeric ethanol extract effectively protects against DEG-induced kidney and liver toxicity in rats.